Usulan Perbaikan Untuk Meminimasi Defect Kurang Center Pada Produk Wire Rod Steel Swrm8 5.5 Mm Unit Wire Rod Mill Pt. Xyz Dengan Metode Six Sigma - Fithratur Rahmi; Agus Alex Yanuar; Marina Yustiana Lubis (eProceedings of Engineering, 2018)
Abstrak Penelitian dilakukan pada PT. XYZ yang merupakan perusahaan maufaktur besi baja. Wire Rod Mill merupakan salah satu unit pada PT. XYZ yang memproduksi Wire Rod Steel salah satunya dengan jenis SWRM8 5.5 mm. Produk Wire Rod Steel memiliki total hasil produksi selama periode Januari 2017 hingga Februari 2018 sebesar 115814 coil dengan jumlah produk defect sebanyak 9878 coil. Fokus penelitian pada defect terbesar yaitu defect kurang center yang terjadi pada mesin Finishing Base Line (FBL). Penelitian ini menggunakan metode Six Sigma dengan tahapan define, measure, analyze, improve, dan control. Tahap define menetapkan alur proses pada Unit Wire Rod Mill PT. XYZ dengan menggunakan SIPOC diagram dan menentukan kriteria produk defect menggunakan Critical to Quality (CTQ). Tahap measure yaitu mengukur stablitas menggunakan peta kontrol p sehingga didapatkan tujuh periode data yang stabil dan mengukur kapabilitas proses sehingga didapatkan rata-rata DPMO sebesar 28753.03 dan rata-rata Level Sigma sebesar 3.39. Tahap analyze dilakukan untuk menganalisis penyebab defect kurang center menggunakan fishbone diagram dan 5 why’s. Penyebab defect kurang center diantaranya posisi roll entry tidak center terhadap pass roll, pergeseran posisi salah satu pass roll, dan posisi antara pass roll bagian atas tidak sejajar dengan pass roll bagian bawah karena operator yang kurang memasang pass roll secara presisi. Tahap improvement yaitu memberikan solusi usulan perbaikan dengan menggunakan FMEA. Solusi perbaikan yang diberikan untuk meminimasi defect kurang center pada produk Wire Rod Steel SWRM8 5.5 mm yaitu melakukan pemeliharaan dan penggantian komponen pass roll setiap 27 hari sekali dan roll entry setiap 28 hari sekali, membuat check sheet pemeliharaan mesin, dan membuat alat bantu pemasangan pass roll. Kata Kunci: Wire Rod Steel, Six Sigma, DMAIC, defect kurang center, FMEA Abstract Research is done at PT. XYZ which is the steel iron manufacturing company. Wire Rod Mill is one of its unit at PT. XYZ which produce Wire Rod Steel type SWRM8 5.5 mm. Wire Rod Steel SWRM8 5.5 mm have total product defects during the period of January 2017 to February 2018 of 9878 defective products of 115814 total products. The focus of this research is on the big defect that is less central defect that occurs in the Finishing Base Line (FBL) machine. Less center defects of the product Wire Rod Steel SWRM8 5.5 mm in Wire Rod Mill Unit PT. XYZ occurs because of roll entry position is not centered on the pass roll because there is no activity of maintaining the roll entry component periodicaly, the fault of one pass roll because there there is no activity of maintaining the pass roll component periodicaly, and the position between the upper pass roll is not parallel to the bottom pass roll because the operator install the pass roll precisely. This research uses Six Sigma method with Define, Measure, Analyze, Improve, and Control (DMAIC) approach. The stage determines the installation process on Wire Rod Mill Unit PT. XYZ by using SIPOC diagram and define the definition of product defect using Critical to Quality (CTQ). The measure stage is the stability measurement using p control chart so as obtain seven periods of stable data and process capability measurement so as obtain the average DPMO of 28753.03 and average Sigma Level of 3.39. Stage analysis was performed to analyze the cause of defects on the use of fishbone diagram and 5 Why’s. The cause of less center defect are the position of roll entry not center to pass roll, shifting ISSN : 2355-9365 e-Proceeding of Engineering : Vol.5, No.2 Agustus 2018 | Page 3022position of one pass roll, and position between top pass roll not parallel to bottom pass roll because operator less pecicelu mount the pass roll. The improvement stage is to provide repair solutions using FMEA. Repaired solutions are to minimize less center defect on Wire Rod Steel SWRM8 5.5 mm such as doing maintenance and replacement of pass roll component at once every 27 days and roll entry component at once every 28 days, make check sheet for maintenance activity, and make support tool for operator while installing pass roll to make it precise. Keywords: Wire Rod Steel, Six Sigma, DMAIC, Less Center Defect, FMEA